Avaliação da resistência de união da resina composta ao esmalte desmineralizado submetido à remineralização e infiltração resinosa de lesão de cárie - Lacerda, Ana Júlia Farias [UNESP] (2015)
The aim of this study was to evaluate, through microtensile test, the bond strength of composite resin restorations made of sound enamel, demineralized, remineralized with saliva, fluoride and infiltratado with resin material, associated with two types of adhesive systems: Total conditioning (Single Bond Universal - AS) and self-etching (Clearfil S3 Bond - AC) and the absence or presence of aging by thermal cycling. We used 240 bovine teeth with enamel surfaces planned, which were divided into 10 groups (n = 12) according to the type of substrate and adhesive system used: G1: (No Treatment) Enamel Healthy + AS; G2: (No treatment) Enamel Healthy + AC; G3: demineralized + AS; G4: demineralized + AC; G5: demineralized + remineralized with Saliva + AS; G6: demineralized + remineralized with Saliva + AC; G7: demineralized + remineralized Fluoride + AS; G8: demineralized + remineralized Fluoride + AC; G9: demineralized + infiltrate with resin (ICON) + AS; G10: demineralized + infiltrate with resin (ICON) + AC. Composite restorations Z-350 and half of the specimens were prepared were subjected to thermal cycling and non-cycling group was only stored for 24 h in distilled water at 37 ºC. For the microtensile test were carried out sections in the teeth to obtain samples adhesive area of about 1 mm2. SEM was performed for further analysis of the adhesive interface. We used the ANOVA three factors (Treatment of Adhesive System Enamel X X Thermal Cycling), followed by the Tukey test (α = 5%). Significant differences were observed for the three factors: treatment of enamel, Adhesive System and Thermal Cycling. The average values in MPa (± standard deviation) for the treatment of enamel factor: Control = 27.34 (± 7.45) a; Demineralized = 11.76 (± 6.69) b; Saliva = 13.78 (± 7.63) b; Fluoride = 15.10 (± 6.86) be ICON = 24.03 (± 7.63) a. For System factor Adhesive: AS = 21.75 (± 13.95) to ...